2007
DOI: 10.1089/oli.2007.0074
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gene Correction with 5′ Acridine-Oligonucleotide Conjugates

Abstract: Single-stranded oligonucleotides (SSOs) mediate gene repair of punctual chromosomal mutations at a low frequency. We hypothesized that enhancement of DNA binding affinity of SSOs by intercalating agents may increase the number of corrected cells. Several biochemical modifications of SSOs were tested for their capability to correct a chromosomally integrated and mutated GFP reporter gene in human 293 cells. SSOs of 25 nucleotide length conjugated with acridine at their 5' end increased the efficiency of gene co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The improvement they obtained was certainly not related to an effect efficiency (x10 on DNA MMR because they made use of the MMR-defective cell line HEK293T (43). Similarly, the efficiency improvement we observed by 5′ acridine modification of LMOs was modest in comparison with observations by others (40), which may also be related to low susceptibility to 5′ end degradation in mESCs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The improvement they obtained was certainly not related to an effect efficiency (x10 on DNA MMR because they made use of the MMR-defective cell line HEK293T (43). Similarly, the efficiency improvement we observed by 5′ acridine modification of LMOs was modest in comparison with observations by others (40), which may also be related to low susceptibility to 5′ end degradation in mESCs.…”
Section: Discussionsupporting
confidence: 54%
“…Finally, we tested an LMO carrying a 9-amino-6-chloro-2-methoxy acridine moiety at its 5′ terminus, which may stabilize the annealing of ssODNs to the target site through DNA intercalation (39). This design was previously found to increase the targeting efficiency up to 65-fold (40). We found that the addition of a 5′ acridine to the 25-nt single-substitution LMO increased the targeting efficiency approximately threefold, resulting in an efficiency of 0.35% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of commonly conjugated units include hydrophobic residues, such as cholesterol and α-tocopherol, or cell-penetrating peptides that enhance membrane penetration [9][10][11][12][13], the polymer PEG, which decreases immunogenicity and enhances serum half-life [14] or intercalating groups to increase hybridization affinity [15]. An extensive literature already describes commonly used oligonucleotide conjugate chemistry, as well as the pharmacokinetic, pharmacodynamic and therapeutic properties of the product oligonucleotide conjugates [16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Other TFO-enhancing elements include nucleotides such as a-L-LNA (Kumar et al, 2006), 2 0 ,4 0 -BNA NC (Rahman et al, 2007(Rahman et al, , 2008, and covalent tethers at the 3 0 or 5 0 end of TFOs such as the d-carboline ligand (Eick et al, 2008) and acridine (De Piedoue et al, 2007). Other DNA intercalators introduced in the middle of a TFO (as in the case of TINA) have been also reported (Osman et al, 2008).…”
Section: Triplex-forming Oligonucleotidesmentioning
confidence: 99%